Effect of pretreatment on decolorization of cashew leaves extracts - Sazali, Noor Emmiey Safieza (2007)
To study the effect of pre-treatment on decolorization of cashew leaves extracts. To study the microbial activities of decolorized Cashew leaves extracts.